(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2024)
Cardiac fibrosis is a critical pathological process underlying numerous cardiovascular diseases and contributes to heart failure and other severe complications. Circular RNAs (circRNAs) have been established as functional regulators of cardiovascular diseases, yet their specific roles in cardiac fibrosis remain unclear. This study was developed to explore the CircHelz/miR-29b regulatory axis in angiotensin II (Ang II)-induced cardiac fibrosis. CircHelz levels in Ang II-induced cardiac fibroblasts (CFs) were detected by qPCR, and siRNA was employed to disrupt its expression. The functional roles of CircHelz were explored through 5-Ethynyl-2¢-deoxyuridine (EdU) uptake, Transwell, and immunofluorescence assays. Bioinformatics and dual-luciferase reporter assays were used to identify and verify CircHelz binding partners. Following Ang II stimulation and CircHelz silencing of mouse CFs, the cells were transfected with anmiR-29b-inhibitor, and the levels of fibrosis-related indicators, cytokines, and adhesion factors were assessed by Western blotting and qPCR. The results showed increased CircHelz expression after Ang II treatment. Mechanistically, CircHelz was identified as an endogenous sponge capable of targeting miR-29b and thereby interfering with its expression. CircHelz silencing promoted proliferation, migration and α-SMA expression in CFs by enhancing the activity of miR-29b, and reduced the expression levels of cardiac fibrosis related indicators. These findings support the ability of CircHelz to bind to miR-29b as a competing endogenous RNA, thereby promoting cardiac fibrosis. As such, CircHelz inhibition holds promise as a therapeutic strategy for Ang II-induced cardiac fibrosis.